2019
DOI: 10.1038/s41467-019-10661-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of epitope abundance reveals the effect of direct and cross-presentation on influenza CTL responses

Abstract: The magnitude of T cell responses to infection is a function of the naïve T cell repertoire combined with the context and duration of antigen presentation. Using mass spectrometry, we identify and quantify 21 class 1 MHC-restricted influenza A virus (IAV)-peptides following either direct or cross-presentation. All these peptides, including seven novel epitopes, elicit T cell responses in infected C57BL/6 mice. Directly presented IAV epitopes maintain their relative abundance across distinct cell types and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 73 publications
(77 reference statements)
6
75
0
Order By: Relevance
“…21 Absolute quantification of pMHCs to date is most commonly performed by comparing endogenous levels of pMHCs to exogenous peptide standards, again failing to account for sample losses. [22][23][24][25] Losses can be accounted for with internal pMHC standards, but require laborious refolding of pMHCs for every target of interest. 21 Nevertheless this approach relies on single point calibration, ignoring the effects of ion suppression, thereby inaccurately estimating absolute pMHC levels in quantitative analyses.…”
Section: Introductionmentioning
confidence: 99%
“…21 Absolute quantification of pMHCs to date is most commonly performed by comparing endogenous levels of pMHCs to exogenous peptide standards, again failing to account for sample losses. [22][23][24][25] Losses can be accounted for with internal pMHC standards, but require laborious refolding of pMHCs for every target of interest. 21 Nevertheless this approach relies on single point calibration, ignoring the effects of ion suppression, thereby inaccurately estimating absolute pMHC levels in quantitative analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to abstract factors driving immunogenicity, viruses offer alternative and attractive systems to study. We have recently investigated the immunopeptidome of vaccinia‐ and influenza A virus‐infected cells, assessing not only what virus‐derived peptides are presented post‐infection, but what fraction of these are immunogenic and allowing insight into parameters that may correlate with these responses . Somewhat surprisingly, we found that the vast majority of vaccinia peptides, and all influenza peptides, were immunogenic in a mouse model of infection, eliciting a hierarchy in terms of their ability to stimulate primed CD8 + T cells ( Figure 2a).…”
Section: Immunopeptidomes Can Be Interrogated By Mass Spectrometrymentioning
confidence: 99%
“…In the vaccinia system >80% of peptides elicited a response in at least one mouse, yet there was skewing of epitopes that were immunogenic in every mouse or that were immunogenic in only a handful of mice, along with a set of peptides that never elicited a response but nevertheless were uniquely presented on infected cells in vitro (Figure 2a). A similar pattern was observed for influenza virus (albeit with less peptides tested, but across more mice and with all peptides eliciting a response in at least one mouse) . These experiments were conducted with inbred mice, raising interesting questions about the nature of priming occurring across individuals—for example, does this suggest a threshold over which immunogenicity can be triggered, and that at lower levels the process is stochastic?…”
Section: Immunopeptidomes Can Be Interrogated By Mass Spectrometrymentioning
confidence: 99%
“…Intranasal priming of B6 mice with x31 generates memory CD8 T cells specific for multiple epitopes in addition to the immunodominant NP366-374 epitope, including two additional immunodominant and at least eight subdominant epitopes [31,32]. Therefore, even if the MT PR8 virus escapes detection from NP366-374-specific CD8 T cells, it remains subject to recognition by CD8 T cells targeting other epitopes.…”
Section: Cd8 T Cell-escaping Mutations Confer a Much Greater Advantagmentioning
confidence: 99%
“…In this study, we aim to quantify the selective advantage of a CD8 T cell-escaping influenza mutant under different contexts related to (i) distinct memory CD8 T cell subsets and (ii) the breadth of memory CD8 T cell responses. The mouse-adapted influenza strain, A/Puerto Rico/8/1934 (H1N1) (PR8), harbors three H-2 b -restricted immunodominant CD8 T cell epitopes [31,32]. We used the wild-type PR8 and PR8 with a point mutation on one of the immunodominant epitopes, NP366-374, such that the peptide-MHCI binding is disrupted and the mutant epitope is not presented [33].…”
Section: Introductionmentioning
confidence: 99%